Circulating sphingolipids and subclinical brain pathology: the cardiovascular health study - Moseholm, Kristine F.; Horn, Jens W.; Fitzpatrick, Annette L.; Djoussé, Luc; Longstreth, W. T.; Lopez, Oscar L.; Hoofnagle, Andrew N.; Jensen, Majken K.; Lemaitre, Rozenn N.; Mukamal, Kenneth J. (Frontiers in Neurology, 2024)
Background: Sphingolipids are implicated in neurodegeneration and neuroinflammation. We assessed the potential role of circulating ceramides and sphingomyelins in subclinical brain pathology by investigating their association with brain magnetic resonance imaging (MRI) measures and circulating biomarkers of brain injury, neurofilament light chain (NfL) and glial fibrillary acidic protein (GFAP) in the Cardiovascular Health Study (CHS), a large and intensively phenotyped cohort of older adults. Methods: Brain MRI was offered twice to CHS participants with a mean of 5 years between scans, and results were available from both time points in 2,116 participants (mean age 76 years; 40% male; and 25% APOE ε4 allele carriers). We measured 8 ceramide and sphingomyelin species in plasma samples and examined the associations with several MRI, including worsening grades of white matter hyperintensities and ventricular size, number of incident brain infarcts, and measures of brain atrophy in a subset with quantitative measures. We also investigated the sphingolipid associations with serum NfL and GFAP. Results: In the fully adjusted model, higher plasma levels of ceramides and sphingomyelins with a long (16-carbon) fatty acid were not significantly associated after correction for multiple comparison with worsening of ventricular size over 5 years and were robustly associated with higher blood levels of NfL ( = 0.05, false-discovery rate corrected P (PFDR) = 0.004 and  = 0.06, PFDR = <0.001, respectively). In contrast, sphingomyelins with very long (20-, and 22-carbon) fatty acids tended to have an inverse association with levels of circulating NfL. In secondary analyses, we found an interaction between ceramide d18:1/20:0 and sex (P for interaction = <0.001), such that ceramide d18:1/20:0 appeared associated with higher odds for infarcts, primarily in women (OR = 1.26 (95%CI: 1.07, 1.49), PFDR = 0.03). We did not observe any associations with GFAP blood levels, white matter grade, mean bilateral hippocampal volume or total brain volume. Conclusions: Overall, our comprehensive investigation supports the evidence that ceramides and sphingomyelins are associated with increased aging brain pathology and that the direction of association depends on the fatty acid attached to the sphingosine backbone.